12t+6-6t=-6

Simple and best practice solution for 12t+6-6t=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12t+6-6t=-6 equation:


Simplifying
12t + 6 + -6t = -6

Reorder the terms:
6 + 12t + -6t = -6

Combine like terms: 12t + -6t = 6t
6 + 6t = -6

Solving
6 + 6t = -6

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 6t = -6 + -6

Combine like terms: 6 + -6 = 0
0 + 6t = -6 + -6
6t = -6 + -6

Combine like terms: -6 + -6 = -12
6t = -12

Divide each side by '6'.
t = -2

Simplifying
t = -2

See similar equations:

| .4x-6=12 | | x^4-x^2-0.1x+0.1=0 | | .35+.50=13.45 | | 3x-5y=27 | | 125y^4-45y^2= | | (5x+4)(2x^2-17x-9x)=0 | | t^3-9t^2+27t-27=0 | | 0.01x^2-154x+525300=0 | | 3(x+9)=39+2x | | 200=4f | | 2(n+2)=4(n+2) | | 5y+8=-37 | | 7.08m=-100 | | -0.1x^2+4x-10=0 | | =at^2-4a+2t^2-8 | | 5x-46=46+x | | 8x-56= | | x+3(-8x-37)=4 | | 7ln(x+9)-9lnx=0 | | 3y-5x=27 | | XSQUARED-5+6=0 | | 1.7n=0.22 | | 8x=3y+13 | | 60+120-x+10+x=180 | | 2x-.35=.20 | | 3x^3+2x^2=512 | | 13*3.14= | | log(x)=.61 | | 5(m+n)-(3m+2n)= | | x^2-21x-36=0 | | 5(2+t)=2(t+1) | | 25xsquared-2x-1=0 |

Equations solver categories